Artabotrys brachypetalus Benth.: Evaluation of its traditional uses, phytochemistry, and pharmacological properties - Alfred Maroyi (AOSIS, 2024)
Background: Artabotrys brachypetalus is best known for its edible fruits, but today, it is a well-known medicinal plant. However, there are several uses of the species, some of them known since prehistoric times. Aim: This study compiles the existing information of the traditional uses, phytochemistry and pharmacological properties, and future potential applications of A. brachypetalus. Setting: This review provides an overview of uses and ethnopharmacological properties of A. brachypetalus. Method: Multiple searches on existing literature were carried out on the traditional, medicinal, phytochemistry, and pharmacological properties of A. brachypetalus in online databases such as Scopus, PubMed, Google Scholar, JSTOR, and Science Direct as well as using pre-electronic literature sources obtained from the university library. Results: This study showed that A. brachypetalus is a multipurpose species used as a food plant, source of fibre, firewood, timber, and herbal medicine. Artabotrys brachypetalus serves as a medicinal plant in five countries to treat human and animal diseases, accounting for 55.6% of the countries where the species is naturally found. The phytochemical evaluation of the plant revealed that it contains alkaloids, cyclohexane carboxylic acid, dicarboxylic acid, fatty acids, flavonoids, phenolics, sesquiterpenes, and sugars. The pharmacological assessments showed that the phytochemical compounds isolated from the species and crude extracts demonstrated antifungal, antidiabetic, antiplasmodial, and larvicidal activities. Conclusion: Further research should focus on elucidation of pharmacological, phytochemical, toxicological, in vitro, in vivo and clinical research of the species. Contribution: This study contributes to the existing knowledge about A. brachypetalus that could be useful in bio-prospecting for new health-promoting products required in the primary healthcare delivery system.